THE FEELING OF TIME: BONHOEFFER ON TEMPORALITY AND THE FULLY HUMAN LIFE - Vosloo, Robert (Scriptura, 2008)
This essay explores the notion of temporality in Bonhoeffer’s thought. After an introductory reference to an early text of Bonhoeffer that reveals his passion for movement and the moment, the essay comments briefly on the direction of Emmanuel Levinas’s reflections on temporality. It is argued that both Levinas and Bonhoeffer link their understanding of temporality to otherness and death. The main part of the essay traces Bonhoeffer’s understanding of the timeful nature of reality, with special reference to his Berlin dissertations, Sanctorum Communio and Act and Being, two of his Barcelona sermons, his Ethics and his Prison writings. The last section of the essay offers Bonhoeffer’s timeful engagement with life as a challenge to a reductive economization of time.